2016
DOI: 10.1007/s40291-016-0190-7
|View full text |Cite
|
Sign up to set email alerts
|

Association of Genetic Polymorphisms in the VKORC1 and CYP2C9 Genes with Warfarin Dosage in a Group of Kuwaiti Individuals

Abstract: Our data showed that individuals carrying the wild-type allele of CYP2C9 or VKORC1 rs9923231, rs9934438 or rs2884737 are less sensitive than individuals with the variant alleles of these SNPs and therefore required a higher daily maintenance dose of warfarin. Our study confirms the association between SNPs in CYP2C9 and VKORC1 and warfarin dose tolerance in Kuwaiti patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 29 publications
1
17
0
Order By: Relevance
“…There is scarcity of data to comprehend the patterns of pharmacogenetic variants in the Arab populations. Recent studies reported the distinct occurrence of genetic variants associated with warfarin dosage in Kuwaiti population [3,4]. Other studies described the pharmacogenetic maps of variants associated with warfarin and clopidogrel in Qatari and Omani population [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…There is scarcity of data to comprehend the patterns of pharmacogenetic variants in the Arab populations. Recent studies reported the distinct occurrence of genetic variants associated with warfarin dosage in Kuwaiti population [3,4]. Other studies described the pharmacogenetic maps of variants associated with warfarin and clopidogrel in Qatari and Omani population [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Kuwaiti and close to Saudi (2%), but lower than in other populations of MENA which were between 6-11%, except for Sudanese where this variant was not detected (73,76,88).…”
Section: Prevalence Of the Studied Genetic Variantsmentioning
confidence: 61%
“…Kuwaiti populations (40%) (66,73,77,88). The CYP2C9*2 MAF was comparable to Saudi, Israeli, Jordanian, Egyptian, Kuwaiti, and Turkish populations which were all between 11-14% (66,72,73,77,78,88,89).…”
Section: Prevalence Of the Studied Genetic Variantsmentioning
confidence: 84%
“…However, the study by Alrashid et al [38] was considered of poor quality as there was no reporting of the r 2 value for the dosing model. The sample-size used in some of the studies was less than 100, which is relatively low and may have affected the power of their conclusions [31, 32, 34, 39].…”
Section: Resultsmentioning
confidence: 99%